"We Shall Overcome": First-Person Plural Pronouns From Search Volume Data Predict Protest Mobilization Across the United States. Issue 8 (November 2021) - Adam-Troian, Jais; Bonetto, Eric; Arciszewski, Thomas
Collective action is a key driver of social and political change within societies. So far, the main factor mobilizing individuals into collective action remains the extent to which they feel identified with a protesting group (i.e., social identification). Although the link between social identification and collective action is well-established, current evidence relies mostly on self-report data. To tackle this issue, we combined real-life protest counts in the United States (2017–2020) with online search data (Google Trends) for pronouns indicating a "group" mind-set (first-person plural pronouns; e.g., "we, " "us"). Time series analyses indicated that weekly fluctuations in searches ( N = 164) predict both protest and protester counts over time. Confirmatory mixed models then showed that a 1% increase in pronoun searches was linked with +13.67% protests (95% CI [4.02, 23.32]) and +47.45% protesters (95% CI [26.54, 68.36]) the following week. These original results have important implications for the ecological study and quantification of collective action dynamics in psychology.